2004
DOI: 10.1002/cne.20383
|View full text |Cite
|
Sign up to set email alerts
|

Photic input pathways that mediate the Drosophila larval response to light and circadian rhythmicity are developmentally related but functionally distinct

Abstract: The Drosophila melanogaster larval photosensory organ that mediates the response to light consists of bilaterally symmetrical clusters of 12 photoreceptors. These are distinguished on the basis of expression of the rhodopsins Rh5 and Rh6. The Rh6-expressing cells correspond to the Hofbauer-Buchner (H-B) eyelet found later in the posterior margin of the adult compound eye and recently shown to function as an input pathway in the entrainment of circadian rhythmicity in adult Drosophila. In addition, the axons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 54 publications
(62 reference statements)
3
45
1
Order By: Relevance
“…Because of the limits of the projector's dynamic range, we could not increase the steepness of the gradient without significantly reducing the size of the experimental arena, so we turned to temporal gradients using triangle waveforms to mimic the stimulus received by larvae moving in straight lines on illumination patterns with a steeper linear spatial gradient. In our previous studies of spatial and temporal gradients of temperature (3)(4)(5)(6)(7)(8)(9)14), odor, and carbon dioxide (10, 11), we found that temporal triangle waves evoked the same behavioral responses as linear spatial gradients.…”
Section: Significancementioning
confidence: 64%
See 1 more Smart Citation
“…Because of the limits of the projector's dynamic range, we could not increase the steepness of the gradient without significantly reducing the size of the experimental arena, so we turned to temporal gradients using triangle waveforms to mimic the stimulus received by larvae moving in straight lines on illumination patterns with a steeper linear spatial gradient. In our previous studies of spatial and temporal gradients of temperature (3)(4)(5)(6)(7)(8)(9)14), odor, and carbon dioxide (10, 11), we found that temporal triangle waves evoked the same behavioral responses as linear spatial gradients.…”
Section: Significancementioning
confidence: 64%
“…However, temporal comparisons performed by moving animals, also known as klinotaxis, also can encode spatial information (2). Like most fly larvae, Drosophila larvae are negatively phototactic during most of their development (3)(4)(5)(6)(7)(8)(9). To navigate away from light, the Drosophila larva uses two sets of photosensors, the Rhodopsin-expressing Bolwig's organs (BO) that mediate phototaxis at low light levels and the non-Rhodopsin-expressing class IV multidendritic (md) neurons that respond to intense light levels comparable to direct sunlight (10).…”
mentioning
confidence: 99%
“…The central nervous system was dissected from early foraging third instar larvae staged as above and treated as described previously (Hassan et al, 2005). The primary antibody used was rabbit antiphospho-Histone H3 (1:1000 dilution; catalogue no.…”
Section: Immunohistochemistry and Imagingmentioning
confidence: 99%
“…However, the fifth LN might be involved in RH5-dependent acute larval responses to light, which do not require the PDF ϩ LNs (Hassan et al, 2005;Keene et al, 2011). The entrainment of the fifth LN in the absence of both CRY and the PDF ϩ LNs suggests a direct connection to the visual system, in agreement with its arborization in the larval optic neuropil.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both photoreceptor types are equally able to suppress TIM levels in the LNs after a 2 h light exposure at the beginning of the night (Keene et al, 2011). In contrast, RH5 fibers alone specifically mediate acute larval responses to light (Hassan et al, 2005;Keene et al, 2011), while RH6 fibers alone are specifically required for the development of a serotonergic arborization that also contacts the LNs (Rodriguez Moncalvo and Campos, 2005). That RH6 activation strongly disrupts molecular oscillations in the LNs even in RR was, however, not anticipated.…”
Section: Discussionmentioning
confidence: 99%